Late diagnosis of hepatitis C virus infection in the Chronic Hepatitis Cohort Study (CHeCS): Missed opportunities for intervention. Issue 5 (20th March 2015) - Moorman, Anne C.; Xing, Jian; Ko, Stephen; Rupp, Loralee B.; Xu, Fujie; Gordon, Stuart C.; Lu, Mei; Spradling, Philip R.; Teshale, Eyasu H.; Boscarino, Joseph A.; Vijayadeva, Vinutha; Schmidt, Mark A.; et al.
Abstract : To determine the stage of liver disease at initial diagnosis of hepatitis C virus (HCV) infection, we analyzed data from the Chronic Hepatitis Cohort Study (CHeCS), a large U.S. observational study. We examined the temporal relationships of initial HCV infection diagnosis with cirrhosis—defined by liver biopsy or mean FIB‐4 score >5.88—and time to onset of cirrhotic decompensation in electronic medical records. We determined time in the health system prior to HCV diagnosis and rates of hospitalization and death following HCV diagnosis. Of 14, 717 patients with chronic HCV seen during 2006‐2011, 6, 166 (42%) had a definable time of initial HCV diagnosis. Of these, 1, 056 (17%) patients met our definition for "late diagnosis" with either cirrhosis concurrent with initial HCV diagnosis (n = 550), a first diagnosis of hepatic decompensation before or within 12 months after initial HCV diagnosis (n = 506), or both (n = 314). Patients with late diagnosis had an average of 6 years in the health system before their HCV diagnosis. In a comparison with patients without late diagnosis, hospitalization (59% versus 35%) and death (33% versus 9%) were more frequent among patients with late diagnosis. Among all who died, mean (median) time from initial HCV diagnosis to death was 4.8 (4.2) years. Conclusion : Many CHeCS patients had advanced liver disease concurrent with their initial HCV diagnosis despite many years of engagement with the healthcare system, and these patients had high rates of hospitalization and mortality. (Hepatology 2015;61:1479–1484)